2010
DOI: 10.1039/c0nj00192a
|View full text |Cite
|
Sign up to set email alerts
|

Directionally electrodeposited gold nanoparticles into honeycomb macropores and their surface-enhanced Raman scattering

Abstract: The ordered honeycomb films of dioctadecyldimethylammonium (DODMA + )-encapsulated sandwich-type [(Mn(H 2 O) 3 ) 2 (WO 2 ) 2 -(BiW 9 O 33 ) 2 ] 10À ({Mn 2 Bi 2 W 20 } 10À ) are used as templates to directionally electrodeposit gold nanoparticles into their macropores. Consequently, the prepared hierarchical Au-filled films present a strong surface-enhanced Raman scattering of rhodamine 6G molecules.Scheme 1 The experimental procedure from the fabrication of the honeycomb film at an air/water interface to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 20 publications
0
22
1
Order By: Relevance
“…Combining the BF and vapor deposition processes, silver spikes arrays with triangular sharp have been fabricated showing strong enhanced Raman scattering of rhodamine 6G [220]. Other strategies involve the electrodeposition of gold nanoparticles [221] or the incorporation of the nanoparticles in the polymeric solution [173]. Recently, SERS substrates have been created by in situ generation and immobilization of Ag NPs nanoparticles at the surface of honeycomb films based on PDMAEMA [184].…”
Section: Surface Enhanced Raman Scattering (Sers) Substratesmentioning
confidence: 99%
“…Combining the BF and vapor deposition processes, silver spikes arrays with triangular sharp have been fabricated showing strong enhanced Raman scattering of rhodamine 6G [220]. Other strategies involve the electrodeposition of gold nanoparticles [221] or the incorporation of the nanoparticles in the polymeric solution [173]. Recently, SERS substrates have been created by in situ generation and immobilization of Ag NPs nanoparticles at the surface of honeycomb films based on PDMAEMA [184].…”
Section: Surface Enhanced Raman Scattering (Sers) Substratesmentioning
confidence: 99%
“…Recently, our group has developed a simpler method to construct highly ordered porous honeycomb films of surfactant-encapsulated polyoxometalates at an air/water interface without any moist airflow across the solution surface. [31][32][33] This method can easily transfer the films onto different substrates for further characterization and application, such as directionally electrodepositing gold nanoparticles into honeycomb macropores [34] and preparing freestanding honeycomb films. [35] Herein, we extend the breath-figure method to an amphiphilic ferrocenyl-based oligomer 1 with ferrocene units in the main chain and hydrophobic cholesteryl groups as side chains (Scheme 1; the synthesis and characterization of the oligomer are described elsewhere [36] ).…”
Section: Introductionmentioning
confidence: 99%
“…[10,11] Ab ig advantage of the honeycombs tructures fabricated by the BF methodi st hat the functions of the films can be facilely tuned by engineeringt he starting materials. [33,34] Polyoxometalates (POMs) are ab ig class of polyanions which consist of early transition metals in their highest oxidation states. [23][24][25][26][27] The films containing honeycombs tructures with varying sizes and morphologies have been successfully used as molecular sieves, [28] sensors, [29] superhydrophobic coatings, [30] antibacterial surfaces, [31] cell culture reservoirs, [32] and templates for electrodeposition of Au or Ag particlesfor surface-enhanced Ramanscattering (SERS).…”
Section: Introductionmentioning
confidence: 99%
“…[33,34] Polyoxometalates (POMs) are ab ig class of polyanions which consist of early transition metals in their highest oxidation states. [38][39][40][41] Pioneering work on honeycomb structures formed by SEPs on solid substrates and air/water interfaces have been reported by Wu et al [42] and us, [23] [23,34,43,44] It was found that the type of POM can have obvious influenceo nt he formation of the honeycomb structures. [36,37] Self-assembled structuresc ontaining POMs are currently ah ot topic in supramolecular chemistry and materials science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation